Serious adverse drug events associated with psychotropic treatment of bipolar or schizoaffective disorder: a 17-year follow-up on the LiSIE retrospective cohort study - Truedson, Petra; Ott, Michael; Wahlström, Lisa; Lundqvist, Robert; Maripuu, Martin; Lindmark, Krister; Lieber, Ingrid; Werneke, Ursula (Frontiers in Psychiatry, 2024)
Introduction: Mood-stabilisers and other psychotropic drugs can lead to serious adverse drug events (ADE). However, the incidence remains unknown. We aimed to (a) determine the incidence of serious ADE in patients with bipolar or schizoaffective disorders, (b) explore the role of lithium exposure, and (c) describe the aetiology. Methods: This study is part of the LiSIE (Lithium – Study into Effects and Side Effects) retrospective cohort study. Between 2001 and 2017, patients in the Swedish region of Norrbotten with a diagnosis of bipolar or schizoaffective disorder were screened for serious ADE to psychotropic drugs, having resulted in critical, post-anaesthesia, or intensive care. We determined the incidence rate of serious ADE/1,000 person-years (PY). Results: In 1,521 patients, we identified 41 events of serious ADE, yielding an incidence rate of 1.9 events per 1,000 PY. The incidence rate ratio (IRR) between ADE with lithium present and causally implicated and ADE without lithium exposure was significant with 2.59 (95% CI 1.20-5.51; p=0.0094). The IRR of ADE in patients <65 and 65 years was significant with 3.36 (95% CI 1.63 – 6.63; p=0.0007). Most common were chronic lithium intoxication, oversedation, and cardiac/blood-pressure related events. Discussion: Serious ADE related to treatment of BD or SZD were uncommon but not rare. Older individuals were particularly at risk. The risk was higher in individuals exposed to lithium. Serum lithium concentration should always be checked when patients present with new or unclear somatic symptoms. However, severe ADE also occurred with other mood stabilisers and other psychotropic drugs.